Binding Force Of Land Ownership Certificates In Name-Borne Agreements By Foreign Citizens To Realize Justice - Kasun Japar; Didik Suhariyanto; Ismail Ismail (Ilmu Hukum Prima (IHP), 2025)
Indonesian land law based on the Basic Agrarian Law (UUPA) adheres to the principle of nationality which prohibits foreign citizens (WNA) from owning freehold land.However, the high interest of foreign nationals in property investment has triggered legal smuggling (fraus legis) through nominee agreements, where the name of an Indonesian citizen (WNI) is used on the Certificate of Ownership (SHM) even though the land is controlled by a foreign national. This phenomenon creates a lack of synchronization between das sollen (legal norms) and das sein (societal practice), creating a legal vacuum because nominee agreements are not regulated in the Indonesian civil law system. The main legal issue is the binding force of SHMs from these illegal transactions and how justice is achieved when disputes arise between formal ownership and actual control. This research is a normative legal research with a statute approach and a case approach.. Secondary data consisting of primary, secondary, and tertiary legal materials were collected through library research. The data were analyzed qualitatively by focusing the study on three court decisions, namely Gianyar District Court Decision No. 259/Pdt.G/2020/PN. Gin, Denpasar District Court Decision No. 274/Pdt.G/2020/PN. Dps, and Gianyar District Court Decision No. 137/Pdt.G/2021/PN. Gin, to understand the judge's considerations in name-borrowing disputes. The results of the research show that the agreement to borrow a name by a foreign national is legally void because it does not fulfill the requirements of a lawful cause (Article 1320 of the Civil Code) and violates Article 26 paragraph (2) of the UUPA.The binding power of a SHM is absolute, with the court upholding the certificate as the sole valid evidence, demonstrating formal justice and legal certainty. This situation conflicts with substantive justice, as foreign nationals lose their investments without recourse. The judicial system ultimately prioritizes the integrity of national agrarian law by adhering to the principle of ex turpi causa non oritur actio, which states that no rights can arise from reprehensible acts.